Монголчуудын бүхэл шүүс хөндөхийн ёс учир хийгээд “хишиг хүртээх” зан үйлийн уламжлал: Ritual tradition of sharing meat and the Mongolians’ custom of meat cutting - Гэрэл (Mongolian Studies, 2023)
The author discusses the ancient ritual tradition of sharing meat and the Mongolians’ custom of meat cutting which holds symbolic meaning as analyzed from ‘Chingis-un hishigyn deej’. Since early times, Mongolians have had a unique ritual tradition and custom of sharing meat depending on ranks in a tribe. Also there are special rules regarding which bones should be eaten by whom.